Dielectric And Optical Properties Of Polar And Nonpolar Liquids At Different Temperatures - SIDDHARTH P KAMBLE,; Y.S. SUDAKE,; S. S. PATIL,; P.W. KHIRADE,; S.C. MEHROTRA, (International Journal of Pharma and Bio Sciences, 2011)
The present paper reports the study of binary mixtures and their properties over the entire range of composition at temperatures 288, 298, 308 and 318 K. Excess dielectric constant, excess molar volume, excess refractive index, molar refraction and excess molar refraction at different temperatures have been computed from the experimentally measured values of the aforesaid parameters and fitted to the Redlich-Kister equation. Excess dielectric constant, excess refractive indices are positive whereas excess molar volume is negative over entire composition range of Methyl Acetate for all temperatures. The results are discussed in the light of intermolecular interactions occurring in the binary mixture. Estimated coefficients of the Redlich-Kister polynomials and the standard error